Effect of APOE4 and APOE2 genotype on white matter microstructure. (December 2021) - Nir, Talia M.; Nabulsi, Leila; Lawrence, Katherine E.; Villalon‐Reina, Julio E.; Abaryan, Zvart; Gari, Iyad Ba; Zhu, Alyssa H.; Haddad, Elizabeth; Muir, Alexandra M.; Thompson, Paul M.; Jahanshad, Neda
Abstract: Background: The apolipoprotein E4 (APOE4) genotype is a major risk factor for late‐onset Alzheimer's disease (AD). APOE2, on the other hand, has a protective effect. While there is evidence supporting an association between APOE genotype and white matter (WM) microstructure, findings have been inconsistent. Studies assessing AD risk in WM microstructure have largely used diffusion tensor imaging (DTI), but more recent diffusion MRI models may offer additional sensitivity to microstructural properties. Here, we characterized the effects of APOE4 and APOE2 genotypes on WM microstructure in a large, population‐based sample of adults from the UK Biobank. Method: Diffusion MRI data from 17, 896 UK Biobank participants (age range: 45‐80 years; Fig 1a) were analyzed. Ten diffusion measures were derived from 4 models: 1) DTI, 2) the tensor distribution function (TDF), 3) mean apparent propagator MRI (MAPMRI), and 4) neurite orientation dispersion and density imaging (NODDI). Each measure was averaged across voxels within 25 WM regions (Fig 1c). Linear regressions were used to compare regional measures between individuals with an E3E3 genotype and E4 (E3E4+E4E4) or E2 (E2E3+E2E2) carriers, adjusting for age, sex, age‐by‐sex interaction, education, parents with dementia, and the first four genetic ancestry principal components. E4 or E2 carrier‐by‐age interactions were also tested, covarying for APOE genotype. FDR ( q =0.05) was used to correct for multiple comparisons across 25 regions. Result: Compared to E3E3 carriers, E4 carriers showed widespread, yet subtle WM differences (Fig 2). The largest effects were detected with signal‐based model measures that reflect increased mean diffusivity (higher DTI‐MD, higher MSD, lower TDF‐FA). Significant E4‐by‐age interactions were detected with NODDI‐ISOVF, with E4 carriers showing a greater age‐related increase in ISOVF (Fig 3). Compared to E3E3 carriers, E2 carriers showed higher NODDI‐ICVF throughout the WM; differences were not detected with other measures. No significant E2‐by‐age interactions were detected (Fig 4). Conclusion: APOE4 carriers showed microstructural WM differences in measures reflecting less restricted diffusion, which could indicate neuronal loss or inflammation, particularly in posterior WM. Age‐dependent APOE4 effects were only detected with multi‐compartment diffusion measures. Greater neuronal density in APOE2 carriers may suggest a protective effect in WM, which was also detectable only with a multi‐compartment model.